2020
DOI: 10.1097/acm.0000000000003351
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Parenthood Remain Challenging During Surgical Residency: A Systematic Review

Abstract: Purpose To examine common themes and synthesize data surrounding pregnancy and parenthood during surgical residency training. Method The authors conducted a systematic search of the literature in March 2019. They searched MEDLINE, EMBASE, and Scopus, seeking articles published from 2003 to 2018 that focused on pregnancy, parenthood, and the experience of surgical residents. They excluded articles that examined nonsurgical programs, as well as editorials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 41 publications
1
74
0
Order By: Relevance
“…In 2020, Todd et al completed a systematic review of 27 manuscripts on physician pregnancy published between 2003 and 2018 and concluded that high rates of infertility and obstetrical complications and negative attitudes from colleagues were common. 9 The authors recommended formal maternity policies and ongoing discussion with all stakeholders to improve conditions for female surgical residents. Our review expands on these earlier reviews as it was designed to be inclusive of the entire body of medical literature on physician pregnancy from 1964 to date, and to examine publications regarding practicing physician and trainees as well as all physician specialties and surgical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Todd et al completed a systematic review of 27 manuscripts on physician pregnancy published between 2003 and 2018 and concluded that high rates of infertility and obstetrical complications and negative attitudes from colleagues were common. 9 The authors recommended formal maternity policies and ongoing discussion with all stakeholders to improve conditions for female surgical residents. Our review expands on these earlier reviews as it was designed to be inclusive of the entire body of medical literature on physician pregnancy from 1964 to date, and to examine publications regarding practicing physician and trainees as well as all physician specialties and surgical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned 2020 Australian systematic review by Hoffman et al, 9 several large international review articles have been published in recent years, examining pregnancy and parenthood among physicians. 17 19 Many of the barriers identified by our participants appear ubiquitous within medicine globally, including the demanding and inflexible nature of medical work and specialty training, experiences of maternal stigma and discrimination, inadequate parental entitlements, and work/family role conflict. Our participants likewise reported comparable negative impacts on both work and family life, including delayed career progression, reduced income, delayed childbearing, stress, and negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…International research indicates that female doctors tend to have children later in life, 19 22 with higher rates of infertility, 19 , 21 assisted reproduction, 19 and pregnancy complications 19 , 23 than the general population. Australian data are lacking; however, with the rise of graduate-entry programmes, the average age of Australian medical graduates is increasing, inducing overlap of medical training with parenthood.…”
Section: Discussionmentioning
confidence: 99%
“…All collective agreements provide accommodations to pregnant residents, typically from their late second or third trimester onward. This may help mitigate some of the negative effects that overnight and call shifts have on pregnant residents 16,17 ; however, further research would be warranted to see if Canadian residents are using these accommodations during pregnancy.…”
Section: Saskatchewanmentioning
confidence: 99%